Molecular docking and MD simulation approach to identify potential phytochemical lead molecule against triple negative breast cancer [version 2; peer review: 1 approved, 2 approved with reservations] - Arabinda Ghosh; M Manikandan; Abhinand PA; Dicky John Davis G; Pranaya Sankaranarayanan (F1000Research)
Background Triple-negative breast cancers (TNBC) are defined as tumors that lack the expression of the estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). It exhibits unique clinical and pathological features, demonstrates high aggressiveness, and has a relatively poor prognosis and clinical outcome. Objective To identify a novel drug target protein against TNBC and potential phytochemical lead molecules against the identified target. Methods In this study, we retrieved TNBC samples from NGS and microarray datasets in the Gene Expression Omnibus database. We employed a combination of differential gene expression studies, protein-protein interaction analysis, and network topology investigation to identify the target protein. Additionally, the molecular docking and molecular dynamics (MD) simulation studies followed by Molecular Mechanics with Generalised Born Surface Area salvation was used to identify potential lead molecule. Result The upregulated genes with LogFC > 1.25 and P-value < 0.05 from the TNBC gene expression dataset were identified. Androgen receptor (AR) was found to be an appropriate hub target in the protein-protein interaction network. Phytochemicals that inhibit breast cancer target were retrieved from the PubChem database and virtual screening was performed using PyRx against the AR protein. Thereby, the AR was found to be the target protein and 2-hydroxynaringenin was discovered to be a possible phytochemical lead molecule for combating TNBC. Moreover, the AR and the 2-hydroxynaringenin complex showed structural stability and higher binding affinity through molecular dynamics and MM-GBSA studies. Conclusion AR was identified as a hub protein that is highly expressed in breast cancer and 2-hydroxynaringenin efficacy of counter TNBC requires further investigation both in vitro and in vivo.